Growth differentiation factor 9 activates the TGF-β pathway in follicle atresia of Muscovy ducks - Caiyun Huang; Ziyuan Du; Yuzhu Shi; Ningning Sun; Zhihao Zhu; Xuanci Yu; Ang Li (Poultry Science)
ABSTRACT: Muscovy ducks' high broodiness hinders industry growth. Studying broodiness regulation contributes to the theoretical foundation for enhancing reproductive performance in Muscovy ducks. Experiment 1, a total of 18 Muscovy ducks were divided into 2 groups: Laying group (LO) and Broody group (BO). To collect ovaries for morphological and transcriptome analysis. Experiment 2, Primary Muscovy ducks granulosa cells (GC) were isolated and treated with or without GDF9 at appropriate concentrations as indicated. Experiment 3, GC were treated with or without GDF9 in the presence or absence of a receptor inhibitor. The cell viability, cell apoptosis rate and levels of TGF-β pathway were determined. In vivo, there was a gradual disappearance of follicles in the ovaries and accompanied by follicle atrophy and a concentration of cytoplasm in BO group. The transcriptome expression profile revealed a total of 1,185 up-regulated differentially expressed transcripts (DEs) and 1,258 down-regulated DEs in the BO group compared to the LO group. The up-regulated differentially expressed GDF9 is involved in regulating the TGF-β pathway, which is among the top 10 pathways identified through the KEGG pathway analysis (P < 0.05). Additionally, the fluorescence intensity of apoptosis is primarily observed in the granulosa layers of the ovary. Compared to the LO group, the mRNA level of TGF-β pathway and the protein of GDF9 and p-Smad2/3 were increased in ovary of the BO group (P < 0.05). In vitro, GDF9 supplementation demonstrated does-related promotion of GC (P < 0.01). Compared to CTRL group, 12 ng/mL GDF9 supplementation to GC increased the rate of cell apoptosis, the mRNA and protein expression of TGF-β pathway and the apoptosis-related genes. Pretreatment of GC with GDF9-receptor inhibitor largely abrogated the negative function of GDF9 treatment (P < 0.05). In summary, granulosa cell apoptosis leading to follicle atresia in broodiness of Muscovy ducks is associated with GDF9 activation of the TGF-β pathway. This discovery lays a solid foundation for understanding duck follicular development and enhancing egg production in Muscovy ducks.